The Microbiome of the Gastrointestinal Tract of a Range-Shifting Marine Herbivorous Fish - Jones, Jacquelyn; DiBattista, Joseph D.; Stat, Michael; Bunce, Michael; Boyce, Mary C.; Fairclough, David V.; Travers, Michael J.; Huggett, Megan J. (Frontiers in Microbiology, 2018)
Globally, marine species’ distributions are being modified due to rising ocean temperatures. Increasing evidence suggests a circum-global pattern of poleward extensions in the distributions of many tropical herbivorous species, including the ecologically important rabbitfish Siganus fuscescens. Adaptability of a species to such new environments may be heavily influenced by the composition of their gastro-intestinal microbe fauna, which is fundamentally important to animal health. S. fuscescens thus provides an opportunity to assess the stability of gastrointestinal microbes under varying environmental conditions. The gastrointestinal microbial communities of S. fuscescens were characterised over 2,000 km of Australia’s western coast, from tropical to temperate waters, including at its current southern distributional limit. Sequencing of the 16S rRNA gene demonstrated that community composition differed among populations, and similarity of hindgut microbial community decreased with distance. However, the population at the southern distribution limit had similar hindgut microbial communities to one disparate population ~1,100 km to the north and levels of short chain fatty acids, an indicator of microbial fermentation activity, were similar among tropical and temperate locations. These data suggest that flexibility in the hindgut microbiome may play a role in enabling such herbivores to colonise new environments beyond their existing range.